Antioxidant potential of eight phenolic acids using high-performance density functional theory - Duy Quang, Dao; Thi Thuy, Nguyen; Thi Ngoc Anh, Hoang; Thi Thuy Huong, Le; Dinh Hieu, Truong; Minh Quan, Pham; Quoc Long, Pham; Manh Cuong, Nguyen; Lan Phuong, Doan (Vietnam Journal of Science and Technology, 2022)
Phenolic acids are one of the major fractions identified in the extract of several vegetable seed oils which present interesting antioxidant properties. A density functional theory (DFT) study on the antioxidant potential of eight phenolic acids including gallic, vanillic, isovanillic, ferulic, caffeic, b-coumaric, cinnamic, and chlorogenic acids, is presented in this paper. The bond dissociation enthalpies (BDEs) of C–H and O–H bonds, the proton affinities (PA) and the ionization energies (IEs) were calculated in detail by using the LC-wPBE functional coupled with the 6-311++G(d,p) basis set. The standard Gibbs free energies (DrG0) for the scavenging reactions towards HOO· radical were calculated. In addition, the kinetics of H-atom transfer reaction was evaluated. As a result, the chosen long-range corrected DFT LC-wPBE functional is shown as the highly reliable computational approaches in calculating geometrical properties as well as the thermochemical parameters by comparison with CCSD(T)/aug-cc-pVDZ results. The differences of bond length are about 0.1 Angstroms, while the ones of BDE are only from 0.1 to 0.6 kcal/mol. Furthermore, gallic, caffeic, ferulic and chlorogenic acids represent as the most reactive antioxidants in the reaction with HOO· radical in water occurring via H transfer process with the negative DrG0 ranging from -3.3 kcal/mol for caffeic to -5.9 kcal/mol for ferulic compounds. Kinetic calculations in the gas phase based on transition state theory (TST) for the studied compound confirm that chlorogenic acid is shown as the most reactive antioxidant via HAT process with the lowest activation free energy (i.e. 17.9 kcal/mol) and the highest reaction rate (i.e. 4.20 × 10-19 cm3/molecule/s).